Digitalizing the World of English Language Teaching: Dare for Change - Sooria, Mary (International Journal of Psychosocial Rehabilitation, 2020)
English occupies a prominent place among languages that are used in the teaching-learning activities in the world. In a multilingual world, English acts as a link language that would enable people to connect and work together. During the time of pandemic, that has considerably thwarted the conventional mode of education, the language educators are trying to invent creative alternatives to the teaching and learning methods in the field of ELT. The new experiments on the teaching-learning has considerably shifted to the online mode, especially to the conference platforms, in the light of the recent lock down that has been imposed in many countries. This paper attempts to bring out how interactive white boards such as a Jam board and a Zite board can be effectively integrated in to the online teaching platform along with a few tried and tested teaching methods to improve English language skills in a fun filled manner.